2013
DOI: 10.1128/jcm.00320-13
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Treponemal Microbiome of Digital Dermatitis Infections by High-Resolution Phylogenetic Analyses and Comparison with Fluorescent In Situ Hybridization

Abstract: bModern pyrosequencing technology allows for a more comprehensive approach than traditional Sanger sequencing for elucidating the etiology of bovine digital dermatitis. We sought to describe the composition and diversity of treponemes in digital dermatitis lesions by using deep sequencing of the V3 and V4 hypervariable regions of the 16S rRNA gene coupled with species-level taxonomic identification. Treponema-specific 16S rRNA gene PCRs and pyrosequencing were performed on biopsy specimens originating from 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
72
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 35 publications
3
72
0
7
Order By: Relevance
“…Moreover, a range of metagenomic studies have identified the association of specific treponeme phylogroups with DD lesions in Europe, Japan, and the United States (31)(32)(33)(34). In each of these studies, other bacterial genera were identified in DD lesions; however, only for the treponemes were there strong association data across all these studies.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, a range of metagenomic studies have identified the association of specific treponeme phylogroups with DD lesions in Europe, Japan, and the United States (31)(32)(33)(34). In each of these studies, other bacterial genera were identified in DD lesions; however, only for the treponemes were there strong association data across all these studies.…”
Section: Discussionmentioning
confidence: 93%
“…also appears to have different constituents at each of the various stages of development, which may help explain the variability noted in the Treponema spp. visualized from previous fluorescent in situ hybridization studies (33,34,54). The significance of these changes in Treponema species and relative abundance in relation to the possible role of Treponema spp.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers (15,53) have used 16S-based cloning to evaluate the DD microbiome by classic Sanger sequencing, creating at most 1,525 clones from nine bovine feet. Klitgaard et al (54) utilized high-throughput 16S-based 454 sequencing to create 212,827 sequences from 40 cows; however, instead of using universal 16S primers, they utilized a custom Treponema-specific primer to explore the diversity of this bacterial genus in each biopsy specimen (54). Consequently, the relative abundance of the Treponema spp.…”
Section: Discussionmentioning
confidence: 99%
“…The bacteria most often associated with DD are spirochetes of the genus Treponema, which predominate in the deepest regions of DD lesions (7,8). To date, at least 20 different phylotypes have been identified from DD biopsy specimens; among these, Treponema phagedenis-like, Treponema medium/Treponema vincentii-like, Treponema denticolalike, and Treponema pedis phylotypes are highly associated with progression of the disease (9)(10)(11)(12). DD also appears to be highly infectious based on the rapid intra-and interherd spread of the disease (6,13,14).…”
mentioning
confidence: 99%